FRAMEWORK TANGGAP BENCANA KEBAKARAN GEDUNG KAMPUS - Heru Sufianto; Agung Murti Nugroho; M Satya Aditama (Jurnal Koridor, 2018)
Fires in buildings have significant impact on communities both socially and economically. In education facilities, fire incidents have potential impact on research product lost. Fire authorities, practitioners and relevant bodies have been addressed this issue partially on the points of physical aspects and management addressed to fire safety. This study seeks the importance element of a framework that should be implemented comprehensively increasing building fire protection around the clock. Physical assessment on numbers of buildings have been performed, a questionnaire seeking for occupant’s awareness and knowledge toward fire incidents have been disseminated. Meanwhile, fire disaster models from a number of campuss buildings have been reviewed. The study found 4 elements of the fire disaster framework to be considered, including: the occupant’s fire awareness, means of the building, insentives, and control.